EFFECT OF WORK CLIMATE AND WORK FACILITIES ON EMPLOYEE PERFORMANCE AT CLASS I AGRICULTURAL QUARANTINE CENTER BANDAR LAMPUNG - junaidi .; M Rafieq; Nuraeni .; Citra Febriati (Saburai International Journal of Social Sciences and Development, 2021)
Employee performance (work performance) results from work in quality and quantity achieved by an employee in carrying out his duties according to the responsibilities assigned to him. Thus, performance is essential for the organization or organization and the employees themselves. Therefore, employee performance will run effectively if it is supported by motivation and work discipline. The research objective in this thesis is to examine the effect of work motivation and work discipline on employee performance at the Class I Agricultural Quarantine Center in Bandar Lampung. This study used a research sampling method with a total of 97 respondents. The analysis is used using quantitative analysis and data processing using the SPSS program.. The results showed that work motivation positively affects employee performance with an influence contribution of 39.3%. Furthermore, work discipline also positively affects employee performance with an impact contribution of 31.6%. The regression test shows that together there is a positive influence between Work Motivation and Work Discipline on employee performance. The magnitude of the influence of the two variables X1 and X2 on Y is 45.7%, other variables outside of this study influence the remaining 54.3%.